THE APPLICATION OF FARS IN A NATIVE SPEAKER OF ENGLISH AND EFL TEXTS - Imam Munandar (Englisia: Journal of Language, Education, and Humanities, 2015)
The research shows that in term of frequency of segment relation, the NS’s text shows the dominant use elaborative relation. On the other hand, EFL text predomi-nantly employs List relation which is slightly higher from Causal relation which comes in the second place. The NS text also reveals lower degree of explicitness which is indicated by low occurrence of conjunction realized in unmarked way. Hypotaxis in the NS’s text is almost equal in number as parataxis, and by comparison it has higher number of hypotactic relation compared with the EFL text. On the other hand, EFL text shows higher degree of explicitness, which is identified by higher number of conjunctions employment which is mostly realized in unmarked way. All of these features of text can be linked to the types of texts and linguistic and cultural background of the writers. The NS’s text which predominantly uses elaborative relation can be linked to the writer-responsible theory. This is where the writers have responsibility to make their text become as comprehensible as possible. Elaborative relation is purposed to advance the flow of understanding of the text by readers by providing clarification and other relevant information. Higher number of hypotactic relations can be influenced by Aristotelian argumentation which encourages writers to argue their point of view. Low explicitness in NS’s text reflects the higher English proficiency of the writers in making the text become coherent without heavily relying on conjunction. On the other hand, EFL text uses larger number of List and Causal relations which is expectedly found in an argumentative text. Its higher number of unmarked conjunction indicates the writer’s heavy reliance on conjunction in making the text coherent. The lower degree of hypotactic relation is linked to politeness strategy and keeping harmony following the Confucianism tradition of writing. Consequently, paratactic relation is tended to be used to avoid aggressiveness in presenting a point of view.